Colegio Miravaelles, Cizur Menor (Navarra) - Otxotorena, Juan Miguel (2003)
Escuela secundaria: aulas, laboratorios y talleres
Keywords: ESPAÑA; CIZUR MENOR; NAVARRA; ARQUITECTURA EDUCACIONAL; ESCUELAS SECUNDARIAS